The Impoverishment of the American College Student - Kelley, Jacob (Journal of Interdisciplinary Studies in Education, 2023)
The Impoverishment of the American College Student is a recommended text for anyone hoping to gain insight on the current state of higher education finance in the United States. In particular, it provides a rich analysis of the mind-numbing quantity of student loan debt. Koch offers much more than a description and explanation of the situation, though. He is also critiquing the actors and actions that maintain an ecosystem in which this is made possible. He states, “Mainstream higher education organizations actively propagate such views, which are oft-repeated in higher education circles, because they largely excuse institutions from significant blame for most of the affordability and student debt problems that clearly do exist” (p. 213). This book serves as a call to action for leaders in higher education to enact serious and sustainable organizational change to ensure that higher education is equitable for all.